2007
DOI: 10.1109/tit.2006.889723
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Sets, Generalized Reed–Muller Codes, and Power Control for OFDM

Abstract: The use of error-correcting codes for tight control of the peak-to-mean envelope power ratio (PMEPR) in orthogonal frequency-division multiplexing (OFDM) transmission is considered in this correspondence. By generalizing a result by Paterson, it is shown that each q-phase (q is even) sequence of length 2 m lies in a complementary set of size 2 k+1 , where k is a nonnegative integer that can be easily determined from the generalized Boolean function associated with the sequence. For small k this result provides… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
137
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(143 citation statements)
references
References 17 publications
(66 reference statements)
0
137
0
1
Order By: Relevance
“…It implies that the code rate loss induced by choosing distinct sequences is negligible for m ≥ 5, and we are able to obtain a sufficiently large number of distinct sequences from Construction 2. Also, we observed that the code rate R dist for a given m is higher than the ones in any other known near-complementary sequences [15][16] [20].…”
Section: Lemmamentioning
confidence: 99%
See 4 more Smart Citations
“…It implies that the code rate loss induced by choosing distinct sequences is negligible for m ≥ 5, and we are able to obtain a sufficiently large number of distinct sequences from Construction 2. Also, we observed that the code rate R dist for a given m is higher than the ones in any other known near-complementary sequences [15][16] [20].…”
Section: Lemmamentioning
confidence: 99%
“…When t = 0, we realize that the near-complementary sequences from Construction 2 are equivalent to the codewords in Golay complementary sets of size 4 and PMEPR ≤ 4 from Construction 14 in [20]. In the paper, the author indicated the potential of applying a permutation to the m variables in the Boolean function for increasing the number of codewords.…”
Section: Remarkmentioning
confidence: 99%
See 3 more Smart Citations